Malawi : Use of Fund Resources-Request for Emergency Assistance. (IMF Staff Country Reports; Country Report ;, 2002)
This paper assesses Malawi's Use of IMF Resources and Request for Emergency Assistance. The food shortage in early 2002 in Malawi has caused immense human suffering. IMF staff endorses the authorities' decision to undertake large-scale food imports to complement the humanitarian aid efforts. Moreover, as effective targeting mechanisms are not available, the IMF staff supports the provision of a price subsidy as the most efficient way of reaching the poor who do not benefit from humanitarian aid.